Drivers or Drifters? The “Who” and “Why” of Leader Role Occupancy—A Mixed-Method Study - Auvinen, Elina; Huhtala, Mari; Rantanen, Johanna; Feldt, Taru (Frontiers in Psychology, 2021)
This study investigated the reasons that leaders have given for their leader role occupancy. By using a mixed-method approach and large leader data, we aimed to provide a more nuanced picture of how leader positions are occupied in real life. We examined how individual leadership motivation may associate with other reasons for leader role occupancy. In addition, we aimed to integrate the different reasons behind leader role occupancy into the framework of sustainable leader careers and its two indicators: leader’s health (occupational well-being) and performance (measured indirectly as followers’ occupational well-being). The survey data consisted of 1031 leaders from various sectors of working life. Qualitative analysis revealed that leaders mention various factors behind their leader role occupancy, resulting 26 themes. After inductive investigation of the data, theory-driven analysis focused on the sustainable career components (person, context, time) and agency versus non-agency. Qualitative data was quantitized based on the theory-driven categories for statistical analysis. Based on the these analysis, we found out that only Affective-Identity MTL predicted all of the studied reasons behind leader role occupancy, whereas the other motivation types (Non-Calculative MTL, and Social-Normative MTL) did not. All of the reasons for leader role occupancy except non-agentic ones were related to both leaders’ own and their followers’ occupational well-being. Leaders with more person-related and agentic reasons for leader role occupancy experienced better occupational well-being. Person- and context-related and agentic reasons behind leader role occupancy associated also with followers’ occupational well-being, but the associations differed from those of leaders’ well-being: person-related and agentic reasons associated with followers’ exhaustion, but this association was not found among leaders. Our study provided important information for practitioners in the field of human resources and development, as it has shown that if the reasons for leader role occupancy mainly reflect circumstances or other non-person-related reasons, the experienced occupational well-being and person-career fit may remain weak. It is necessary to try to support the leadership motivation for those leaders, or to shape the job description in such a way that it can also offer the experiences of meaningfulness from aspects other than self-realization through a managerial role.